Analisis Pengaruh Produk, Harga, dan Promosi Terhadap Keputusan Menabung pada PT Bank Rakyat Indonesia (Persero) Tbk - Simanjuntak, Anggi Natalinda; Soemarso, Embun Duriany; Muslikh, Moh. (Program Studi Perbankan dan Keuangan Fakultas Ekonomi Universitas Siliwangi, 2023)
This research aims to find out the effect of product, price, and promotion towards saving decision (study of Bank Rakyat Indonesia customer in the Salatiga region) either simultaneously or partially. The population in this research were all customers at PT Bank Rakyat Indonesia (Persero) Tbk in the Salatiga region. The sampling technique used non-probability sampling technique, as many as 100 respondents. The data used in this research are primary data obtained through distributing questionnaires. The data analysis model uses the Multiple Linear Regression Analysis. While the data analysis technique uses the Statistical Test F, the Determination Coefficient Test (R2), and the Statistical Test t. The results of the analysis and discussion show that the product, price, and promotion variables simultaneously have a significant effect towards saving decision at PT Bank Rakyat Indonesia (Persero) Tbk in the Salatiga region. Partially, the product, price, and promotion variables each have a significant effect towards saving decision at PT Bank Rakyat Indonesia (Persero) Tbk in the Salatiga region.